Factors That Influence the Behavioural Intention to Use E-Payments in Indonesia - Rita Rahayu (Ekonomis: Journal of Economics and Business, 2022)
This study aims to investigate the factors that influence the intention to use electronic payment in Indonesia. In this study eights variables were identified as influence factors, they are perceived usefulness, perceived ease of use, consumer’s perception, enjoyment, trust, social influence, perceived security, and attitude toward behaviour. Based on data from 403 respondents collected through online questionnaire which was then analysed by Lisrel 8.8, it was found that six of the eight variables, namely perceived ease of use, enjoyment, trust, social influence, perceived security, and attitude toward behaviour have significant relationship with the behavioural intention to use e-payment system. Furthermore, this study also found that the behavioural intention significantly leads to the e-payment adoption and e-payment adoption also significantly influences the continuance intention to use e-payment